The last mapmaker eaudiobook - Soontornvat, Christina (Spotify Audiobooks, 2022)
A Newbery Honor Book "As assistant to Mangkon's most celebrated mapmaker, twelve-year-old Sai plays the part of a well-bred young lady with a glittering future. In reality, her father is a conman—and in a kingdom where the status of one's ancestors dictates their social position, the truth could ruin her. Sai seizes the chance to join an expedition to chart the southern seas, but she isn't the only one aboard with secrets. When Sai learns that the ship might be heading for the fabled Sunderlands—a land of dragons, dangers, and riches beyond imagining—she must weigh the cost of her dreams. Vivid, suspenseful, and thought-provoking, this tale of identity and integrity is as beautiful and intricate as the maps of old."